Perjanjian Implementasi (Implementing Agreement) Bab XI Konvensi Hukum Laut 1982 - Etty R Agoes (Jurnal Hukum IUS QUIA IUSTUM, 2000)
As a result of lengthy negotiations, the 1982 United Nations Convention on the Law of the Sea, was geared toward the fulfilment for a need of a new dimension in the regulation of the international community's uses of the oceans. However as the new law of the sea is a result of a "give and take' process, of a series of accomodation, its implementation is hindered by the argument that its provisions have not given enough accomodation to theexisting conditions. Such argument mostly came from the developed countries, in particular to the issue of deep sea-bed mining exploitation. The Implementing Agreement to Part XI of the Convention is a breakthrough to overcome these problems.